Al-Qasas Al-Nabawi Dalam Karya Abu Ishaq Al-Huwayni Dan ‘Umar Sulayman Al-Ashqar: Kajian Perbandingan - Muhammad Arif Yahya; Khairulnazrin Nasir; Muhammad Ikram Abu Hassan (USIM Press, 2024)
Vol 6. No. 2 (December 2021)